«Камена» Миколи Зерова (1924 року): аспекти цілісності - Якубчак, Н. (Літературознавчі обрії. Праці молодих учених, 2010)
The integrity aspects of Mykola Zerov’s poetic book «Kamena» (1924), namely textual interactions between verses in cycles and the book in general are analyzed in the article. The aim of the study is to prove that «Kamena» is not a simple collection of verses arranged in an incidental order but a cyclic phenomenon which has an important intertextual cohesion.